2015
DOI: 10.1007/s11356-015-4701-6
|View full text |Cite
|
Sign up to set email alerts
|

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease

Abstract: Inhalation of silica (SiO2) in occupational exposures can cause pulmonary fibrosis (silicosis), lung function deficits, pulmonary inflammation, and lung cancer. Current risk assessment models, however, cannot fully explain the magnitude of silica-induced pulmonary disease risk. The purpose of this study was to assess human health risk exposed to airborne silica dust in Taiwan ceramics manufacturing. We conducted measurements to characterize workplace-specific airborne silica dust in tile and commodity ceramic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It has been verified that prolonged inhalation of crystalline silica may cause lung inflammation and lead to multiple diseases, such as chronic bronchitis, lung fibrosis, and silicosis [38,39]. The expression of COX-2 and PGs has been observed to be significantly induced in inflammatory pulmonary diseases such as COPD, acute lung injury, and asthma [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been verified that prolonged inhalation of crystalline silica may cause lung inflammation and lead to multiple diseases, such as chronic bronchitis, lung fibrosis, and silicosis [38,39]. The expression of COX-2 and PGs has been observed to be significantly induced in inflammatory pulmonary diseases such as COPD, acute lung injury, and asthma [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that prolonged inhalation of crystalline silica can lead to lung inflammation and the development of various diseases, including chronic bronchitis, lung fibrosis, and silicosis [38,39]. Moreover, the expression of COX-2 and PGs has been observed to be significantly induced in inflammatory pulmonary diseases such as COPD, acute lung injury, and asthma [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The variances of occupational health and safety practices between developed and developing countries should be concerned. The risk of inflammation is higher in workers those exposed to more silica due to longer duration of work and as the exposure lasts pulmonary diseases such as pneumoconiosis and fibrosis might occur (7,14).…”
Section: Discussionmentioning
confidence: 99%
“…As the employment in coal mining industry has declined recently, cases of silicosis began to be reported from sectors such as sandblasting, stone breaking, construction, mining, cement and glass production. The ceramics industry is also one of the sectors where silicosis cases commonly reported (7). It has been shown that exposure levels for crystalline silica have exceeded and were associated with high exposure levels almost in all ceramic process steps such as raw material preparation, mixing, molding, casting and retouching (8).…”
Section: Introductionmentioning
confidence: 99%